2020
DOI: 10.4314/ovj.v10i1.12
|View full text |Cite
|
Sign up to set email alerts
|

<I>Giardia duodenalis</I> infection in dogs affected by primary chronic enteropathy

Abstract: Background: Canine primary chronic enteropathy (CE) includes a heterogeneous group of diseases characterized by chronic gastrointestinal signs.Aim: This study evaluated the occurrence of Giardia duodenalis infection in primary CE-affected dogs.Methods: Forty-seven CE-affected dogs of different age and sex were enrolled in the study. For each dog, frequency of defecation, fecal consistency, and eventual fecal abnormalities were evaluated. A clinical scoring index of CE severity (clinical chronic enteropathy act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
(53 reference statements)
2
7
0
1
Order By: Relevance
“…In a murine model of infection, animals infected neonatally did not clear the parasite when they reached adulthood, although naive adult animals exposed to G. intestinalis were resistant to infection, suggesting that G. intestinalis manipulated the host during the postnatal period to favor its own persistence [ 42 ]. Genotyping results revealed that puppies were infected by assemblages C and D, and that multi-infections were frequent, confirming previous observations [ 12 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…In a murine model of infection, animals infected neonatally did not clear the parasite when they reached adulthood, although naive adult animals exposed to G. intestinalis were resistant to infection, suggesting that G. intestinalis manipulated the host during the postnatal period to favor its own persistence [ 42 ]. Genotyping results revealed that puppies were infected by assemblages C and D, and that multi-infections were frequent, confirming previous observations [ 12 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…From the detailed examination of the genotypes identified in the different dog populations examined in the various studies performed in Italy, including the present study, a high variability in the frequency of canine and potentially zoonotic genotypes can be observed. More specifically, it emerges that in some studies, potentially zoonotic genotypes were [29,30] or were not [24,32,34,35] identified among privately owned dogs, while in other studies, potentially zoonotic genotypes appeared to be prevalent or showed a high prevalence among kennel or stray dogs [23,25], or were almost completely absent [26,33]. Moreover, this variability additionally emerged by the comparison of G. duodenalis geno-types in the different kennels here examined, as potentially zoonotic genotypes were identified in all of them, while canine genotypes were present in only two of them.…”
Section: Discussionmentioning
confidence: 99%
“…Several limitations to this pilot study need to be acknowledged, some of which pertain to the diagnostic exclusion protocol, whereas others to the dietary trial itself. With respect to the former, our strategy of excluding infected animals from the diagnostic work-up due to the risk of re-infestation after parasiticidal therapy might have caused a loss of other CIE cases within the study population, being intestinal parasitoses of common occurrence in primary CIE-affected dogs [ 97 ]. Furthermore, the lack of a complete dietary history in all patients belonging to the study group might have contributed to CIE phenotype misclassification.…”
Section: Discussionmentioning
confidence: 99%